Supplementation of hyaluronic acid injections with vitamin D improve knee function by attenuating synovial fluid oxidative stress in osteoarthritis patients with vitamin D insufficiency - Shen, Jianlin; Lin, Xiaoning; Lin, Yujin; Xiao, Jiecheng; Wu, Changfu; Zheng, Feng; Wu, Xianwei; Lin, Haibin; Chen, Guoli; Liu, Huan (Frontiers in Nutrition, 2023)
Objectives: There is still controversy about the effect of vitamin D supplementation on osteoarthritis (OA). The purpose of this study was to investigate the effects of vitamin D supplementation with Hyaluronic acid (HA) injection on OA. Methods: We investigated serum vitamin D levels and oxidative stress (OS) in synovial fluid from patients with OA who underwent total knee arthroplasty (grade IV, n=24) and HA injection (grade II and III, n=40). The effects of HA injection with or without oral vitamin D supplementation on synovial fluid OS and knee pain and function were then further investigated. Finally, patients underwent HA injection were divided into two groups according to vitamin D levels (vitamin D=30 ng/ml), and the efficacy of the two groups were compared. Results: The results showed that the levels of glutathione peroxidase (GSH-PX) (P<0.05) in the synovial fluid were lower in patients with stage IV OA than that in patients with stage II-III OA, while the levels of malondialdehyde (MDA) (P<0.05) and lactate dehydrogenase (LDH) (P<0.01) were significantly higher. Moreover, we found that age, BMI and vitamin D levels were significantly associated with the levels of oxidants and/or antioxidants in synovial fluid, and that vitamin D was significantly negatively correlated with BMI (R=-0.3527, p=0.0043). Supplementation of HA injections with vitamin D significantly reduced the OS status in synovial fluid, attenuated knee pain and improved knee function in OA patients with vitamin D insufficiency. Conclusion: We conclude that maintenance of vitamin D sufficiency may be beneficial for the treatment of OA by improving OS in synovial fluid.